Biotic and Abiotic Stresses Activate Different Ca2+ Permeable Channels in Arabidopsis - Cao, Xiao-Qiang; Jiang, Zhong-Hao; Yi, Yan-Yan; Yang, Yi; Ke, Li-Ping; Pei, Zhen-Ming; Zhu, Shan (Frontiers in Plant Science, 2017)
To survive, plants must respond rapidly and effectively to various stress factors, including biotic and abiotic stresses. Salinity stress triggers the increase of cytosolic free Ca2+ concentration ([Ca2+]i) via Ca2+ influx across the plasma membrane, as well as bacterial flg22 and plant endogenous peptide Pep1. However, the interaction between abiotic stress-induced [Ca2+]i increases and biotic stress-induced [Ca2+]i increases is still not clear. Employing an aequorin-based Ca2+ imaging assay, in this work, we investigated the [Ca2+]i changes in response to flg22, Pep1 and NaCl treatments in Arabidopsis thaliana. We observed an additive effect on the [Ca2+]i increase which induced by flg22, Pep1 and NaCl. Our results indicate that biotic and abiotic stresses may activate different Ca2+ permeable channels. Further, Calcium signal induced by biotic and abiotic stresses was independent in terms of spatial and temporal patterning.